2018
DOI: 10.1111/jch.13416
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and 24‐hour ambulatory blood pressure in adults not on antihypertensive medications

Abstract: Short sleep duration has been widely linked to increased cardiovascular morbidity and mortality. We performed a post-hoc analysis of 24-hour ambulatory blood pressure monitoring (ABPM) in the Lifestyle Modification in Blood Pressure Lowering Study (LIMBS) and Penn Icelandic Sleep Apnea (PISA) Study. The 24-hour mean systolic blood pressure was 12.7 mmHg higher in LIMBS (p<0.001; n=66) and 4.7 mmHg higher in PISA (p=0.005; n=153) among participants with shorter sleep duration (less than seven hours) compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…PISA was an observational prospective trial assessing clinical and molecular factors responsible for BP changes associated with obstructive sleep apnea. The authors found that the 24‐hour mean systolic BP was 12.7 mm Hg higher in LIMBS and 4.7 mm Hg higher in PISA study among participants with short sleep duration, defined as less than seven hours of sleep per night, in comparison with those with longer sleep, independently of nocturnal and in‐office BP . These findings confirm and build up the existing body of knowledge whereby daily sleep duration affects health outcomes.…”
Section: Sleep Duration Blood Pressure and Beyondsupporting
confidence: 65%
“…PISA was an observational prospective trial assessing clinical and molecular factors responsible for BP changes associated with obstructive sleep apnea. The authors found that the 24‐hour mean systolic BP was 12.7 mm Hg higher in LIMBS and 4.7 mm Hg higher in PISA study among participants with short sleep duration, defined as less than seven hours of sleep per night, in comparison with those with longer sleep, independently of nocturnal and in‐office BP . These findings confirm and build up the existing body of knowledge whereby daily sleep duration affects health outcomes.…”
Section: Sleep Duration Blood Pressure and Beyondsupporting
confidence: 65%
“…Unfortunately, lines of evidence pointed to the adverse effect of low‐quality sleep on blood pressure, and this association appears stronger in middle‐aged adults and in women 22 . For example, the 24‐h mean systolic blood pressure was 12.7 mmHg higher among participants with shorter sleep duration (less than 7 h) compared to those with longer sleep duration (at least 7 h) 23 . Nevertheless, all the studies mentioned above did not focus on pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, sleep quality seems to play an important role in BP control 6 with short sleep duration or poor sleep efficacy being associated with hypertension developing 7 . Sleep deprivation increases BP by changing cardiovascular autonomic modulation, mainly impairing baroreflex control and increasing cardiac sympathovagal balance 8 .…”
Section: Introductionmentioning
confidence: 99%